The machinery underlying malaria parasite virulence is conserved between rodent and human malaria parasites - Mariana De Niz (Nature Portfolio, 2016)
Proteins SBP1 and MAHRP1 of the human malaria parasite are required for sequestration of infected red blood cells in major organs. Here, De Niz et al. identify homologous proteins in the rodent parasite Plasmodium berghei, showing that they play similar roles and supporting the usefulness of malaria mouse models.